Implementation of Tahfidz Juz 29 Program with Dzikroni Method in Class VIII A at MTs Muhammadiyah Waru Baki Sukoharjo Academic Year 2025/2026 - Riko Iman Pramudya; Shokhibul Mighfar; Hakiman (Literacy: Journal of Education and Social Science, 2025)
The erosion of students’ religious character in Islamic schools has become an urgent educational challenge, particularly in fostering discipline, moral awareness, and respectful behavior. This study investigates how religious character is cultivated among eighth-grade students at MTs Darul Ma'arif Purwodadi in the 2024/2025 academic year and evaluates the effectiveness of institutional religious habituation programs. Using a qualitative case study design, data were collected through classroom observations, semi-structured interviews with teachers and students, and institutional documentation. Data were analyzed using an interactive model of data reduction, data display, and verification, with triangulation applied to ensure trustworthiness.The results indicate that religious character formation is facilitated through an integrated system of religious habituation, including Asmaul Husna recitation, Qur’anic literacy (BTQ), congregational prayers, and regular Qur’an recitation. These practices, supported by consistent teacher supervision and role modeling, contribute to increased religious awareness, improved discipline, and more positive student behavior. However, variations in student engagement and self-discipline suggest the need for more individualized reinforcement strategies. This study contributes to Islamic education literature by demonstrating how structured religious routines and pedagogical modeling can serve as an effective framework for character education in madrasah settings